HUBUNGAN KADAR VITAMIN D SERUM DENGAN INTENSITAS NYERI PADA NYERI KRONIK - Rahmi Ardhini,* Dani Rahmawati,* Dwi Pudjonarko,* Endang Kustiowati* (NEURONA, 2015)
INTRODUCTION VITAMIN D DEFICIENCY IS A RISK FACTOR FOR CHRONIC PAIN SEVERAL STUDIES LINKING VITAMIN D LEVELS WITH CHRONIC PAIN HAD VARYING RESULTS FURTHER STUDY IS NEEDED TO DETERMINE THE RELATIONSHIP BETWEEN VITAMIN D LEVEL AND PAIN INTENSITY IN CHRONIC NONCANCER PAINTHAT HAD BEEN TREATED USING ANALGESICS